Enhancing Accountability in Religious Institutions: A Conceptual Model of PSAK 45 Application in Mosques - Muhammad Bahrul Ilmi; Dini Cantika Marpaung (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to determine the effects of financial statement quality and the jamaah trust on the conceptual model of PSAK 45 in Yogyakarta. PSAK 45 is a Statement of Financial Accounting Standards that focuses on the Financial Reporting of Nonprofit Entities and was ratified by the Financial Accounting Standards Board on April 8, 2011. Mosques are nonprofit organizations used for worship and for all activities related to the people. For this reason, mosques require an accounting process that produces an effective financial reporting system and provides all the information supporting worship facilities and religious activities, including maintenance and repair activities. Financial statements play an important role in presenting information generated by the Mosque's activities and operations. The quality of financial reports is an important factor for mosque organizations, as they can demonstrate that the takmir are properly accountable for the authority granted to them as a mandate to manage funds or assets originating from the congregation or the community. The results show that the quality of the financial statements and the Jamaah trust are affected by the conceptual model of PSAK 45.